Genetic and molecular origins of colorectal Cancer among the Iranians: an update - Mohammad Reza Abbaszadegan; Meysam Moghbeli (BMC, 2018)
Abstract Background Colorectal cancer (CRC) is one the leading causes of cancer related deaths among Iranians. Despite the various progresses in new therapeutic methods, it has still a low rate of survival. This high ratio of mortality is mainly related to the late diagnosis, in which the patients refer for treatment in advanced stages of tumor. Main body colorectal cancer progression is largely associated with molecular and genetic bases. Although Iran has a high ratio of CRC mortality, there is not an efficient genetic panel for detection and prognosis. Therefore, it is critical to introduce new diagnostic markers with ability to detect in early stages. Conclusion Present review summarizes all of the genetic and epigenetic factors which are reported in CRC until now among the Iranian patients to pave the way of incorporation of new ethnic specific markers into the clinical practice and development of new targeted therapeutic methods.